Occupational risk factors for Carpal Tunnel Syndrome among nurses in medical - Anuar Ithnin,; Dinnee, Kong; Saraswathy Venkataraman, (Universiti Kebangsaan Malaysia, 2012)
Carpal tunnel syndrome (CTS) is a hand disorder which indicates the presence of symptoms such as pain, numbness, and muscle weakness among the patient. CTS is an occupational related disorder which can occur in any profession. However, it can be prevented and managed. The aims of the research were to determine the prevalence of acquiring CTS among nurses who worked in the wards and occupational risk factors involving the upper limbs during nursing tasks performance. The specific aims were to determine the relationship between the prevalence of acquiring CTS and individual factors (age, gender, race, educational level, duration of work and medical history), relationship between the prevalence of acquiring CTS and occupational risk factors in nursing tasks. Nurses profession was chosen as they are performing multitask involving upper limbs especially the wrist joints.